Persistent eosinophilia among 21 historic cases of Strongyloides stercoralis infection: a case for routine follow-up and repeat treatment. (5th November 2019) - Arkell, Paul; Cosgrove, Catherine; Riley, Peter
Abstract: Background: Strongyloidasis affects more than 100 million people worldwide and causes persisting infection. Methods: We retrospectively reviewed 21 cases of parasitologically confirmed Strongyloides stercoralis infection at our centre. Results: We found four individuals who had eosinophilia (>0.5x10 9 /litre) more than 6 mo after treatment. Conclusions: This may represent ongoing or relapsed infection. Our data support the need for continued follow-up of treated individuals, particularly those with abnormal host defences who are at risk of severe forms of the disease.